The intensity side of volition - A theoretical and empirical overview of effortful striving - Brinkmann, K.; Richter, M.; Gendolla, G. H. E. (Zeitschrift für Sportpsychologie, 2021)
Attaining sports or health goals requires not only high motivation but also the willpower to translate sport-behavior intentions into successful action. This volitional regulation calls for the mobilization of effort to overcome obstacles in the pursuit of goals. The present article provides a theoretical and empirical overview of motivation intensity theory (Brehm & Self, 1989) - a conceptual framework that makes clear and testable predictions about effort mobilization in various contexts. First, we present the guiding principles of this theory and its operationalizations by measures of effort-related cardiovascular reactivity and physical handgrip force. Second, we review a selection of empirical tests of the basic assumptions of this theory and the impact of psychological moderator variables such as affect, fatigue, pain, and personality on effort mobilization. Finally, we discuss important implications of these findings for the sports and health domains and make suggestions for future research.